2006
DOI: 10.1073/pnas.0510909103
|View full text |Cite
|
Sign up to set email alerts
|

Cockayne syndrome group B protein (CSB) plays a general role in chromatin maintenance and remodeling

Abstract: Cockayne syndrome (CS) is an inherited neurodevelopmental disorder with progeroid features. Although the genes responsible for CS have been implicated in a variety of DNA repair-and transcription-related pathways, the nature of the molecular defect in CS remains mysterious. Using expression microarrays and a unique method for comparative expression analysis called L2L, we sought to define this defect in cells lacking a functional CS group B (CSB) protein, the SWI͞SNF-like ATPase responsible for most cases of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 58 publications
8
130
0
2
Order By: Relevance
“…The similar impairment of 8-OH-Gua repair reported in the absence of CSB (reviewed by Licht et al, 2003) or CSA (this study) suggests that these proteins act in the same pathway. We favor the hypothesis that the acceleration of repair at early repair times mediated by CSB (Osterod et al, 2002) or CSA (this study) reflects the role of CS proteins in the regulation of chromatin structure (for instance by ubiquitination and/or acetylation of histones) (Citterio et al, 2000;Groisman et al, 2003;Newman et al, 2006). CS-mediated chromatin remodeling activity might increase the accessibility of DNA damage to the repair machinery.…”
Section: Discussionmentioning
confidence: 60%
“…The similar impairment of 8-OH-Gua repair reported in the absence of CSB (reviewed by Licht et al, 2003) or CSA (this study) suggests that these proteins act in the same pathway. We favor the hypothesis that the acceleration of repair at early repair times mediated by CSB (Osterod et al, 2002) or CSA (this study) reflects the role of CS proteins in the regulation of chromatin structure (for instance by ubiquitination and/or acetylation of histones) (Citterio et al, 2000;Groisman et al, 2003;Newman et al, 2006). CS-mediated chromatin remodeling activity might increase the accessibility of DNA damage to the repair machinery.…”
Section: Discussionmentioning
confidence: 60%
“…Different approaches provide evidence that CSB might have an impact on transcription itself. Transcriptome analysis of CS-B cells revealed deregulation of gene expression similar to that caused by agents that disrupt chromatin structure [35]. When added to a stalled RNAPIIo (at a CPD photolesion) CSB can stimulate transcription elongation by addition of one nucleotide to the nascent transcript, but not bypass of the lesion [36].…”
Section: Transcription-coupled Nucleotide Excision Repair Requires Spmentioning
confidence: 99%
“…A study by Egly and co-workers (Proietti-De-Santis et al, 2006) supports a role for CSB in regulating the transcription pattern after UV damage as they found a function for CSB in transcription from some but not other promoters. Another comparative gene expression study established that CSB is involved in transcription of genes involved in chromatin maintenance and remodeling (Newman et al, 2006). CS cells display a stronger apoptotic response to DNA damaging agents than normal cells Laposa et al, 2007;Liu et al, 2006), which in part could explain why no cancer is seen in the patients.…”
Section: The Role Of Csb In Various Cellular Processesmentioning
confidence: 99%
“…When compared to CSB deficient cells, the transcription from chromatin in wild type cells was more resistant to the detergent Triton X-100, indicating that the transcription machinery is less tightly associated with chromatin in CSB deficient cells compared to wild type cells (Balajee et al, 1997). A study by Weiner and coworkers found that the transcription pattern of CSB deficient cells had a significant overlap with the transcription pattern of cells treated with the histone deacetylase (HDAC) inhibitor trichostatin A (TSA), indicating that CSB could play a role in chromatin maintenance (Newman et al, 2006). The similarity of HDAC inhibited cells to CSB deficient cells indicates that a role of CSB is to decrease the amount of histone acetylation.…”
Section: Csb and Chromatin Structurementioning
confidence: 99%